Can Digital Footprints Lead to Greater Financial Inclusion? - Kumar, Kabir; Muhota, Kim (Washington, DC: World Bank, 2012)
Poor people's use of their mobile phones generates data that leave what can be called a digital footprint. These data are among a handful of sources of electronic information that exist on poor people. This information is potentially powerful but has not yet been used in ways to radically impact financial access for poor people. This brief highlights some early experience on the potential of digital footprints from mobile phone use. Most of this initial work is experimental. As long as consumer interests are protected and privacy, security, and ethical use concerns are addressed, these data may become a useful way to reach unbanked poor people with a range of financial products.